2014
DOI: 10.1517/14712598.2014.900537
|View full text |Cite
|
Sign up to set email alerts
|

An update on new adoptive immunotherapy strategies for solid tumors with cytokine-induced killer cells

Abstract: Since our last review, much effort has been made to improve CIK cell cytotoxicity and clinical effectivity. Targeted CIK cell therapy and combinations of CIK cells with antiangiogenic drugs or oncolytic viruses are examples of recent outstanding achievements in the field of adoptive CIK cell therapy. The clinical application of CIK cells in combination with conventional therapies, especially, obtained promising results. However, the best combination and the optimal therapy schedule have yet to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…26 Our exploratory analysis of phenotypic changes in circulating T-cell subpopulations did not demonstrate significant changes in Treg, activated CTLs, activated B cells, or NK cells in the peripheral blood after therapy with OrienX010 (data not shown). Ex vivo and in vivo experimental evidence has shown that CIK cells generated with a "cytokine cocktail" 16,17 resulting in CIK cells with a high level of cytotoxic activity in a broad range of tumor cell lines 18 and co-culture with DCs has elicited an increase in the antitumor activity of CIK cells. 22 Thus, the combination of DCs and CIKs can lead to an increase in cytotoxic activity, more effective than either treatment alone, 23 and have demonstrated encouraging clinical signals supporting investigation in a variety of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our exploratory analysis of phenotypic changes in circulating T-cell subpopulations did not demonstrate significant changes in Treg, activated CTLs, activated B cells, or NK cells in the peripheral blood after therapy with OrienX010 (data not shown). Ex vivo and in vivo experimental evidence has shown that CIK cells generated with a "cytokine cocktail" 16,17 resulting in CIK cells with a high level of cytotoxic activity in a broad range of tumor cell lines 18 and co-culture with DCs has elicited an increase in the antitumor activity of CIK cells. 22 Thus, the combination of DCs and CIKs can lead to an increase in cytotoxic activity, more effective than either treatment alone, 23 and have demonstrated encouraging clinical signals supporting investigation in a variety of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…11 DC are potent antigen-presenting cells, promoting the generation of tumor antigen-specific helper and cytotoxic T cells, inducing antitumor immune responses. [12][13][14][15] Ex vivo and in vivo experimental evidence has demonstrated that cytokineinduced killer (CIK) cells generated with a "cytokine cocktail" 16,17 result in CIK cells with a high level of cytotoxic activity in a broad range of tumor cell lines, supporting their use for adoptive immunotherapy and have yielded encouraging results. [18][19][20] It is hypothesized that the tumorspecific cellular components of CIK therapy may be responsible for the clinical benefits observed in some cancer patients who receive this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that AuNPrs could be used as nanoheaters, which transform the NIR photons they absorbed into heat and then kill the cancer cells [53]- [55]. It is very necessary to assess the lightthermal conversion efficiency in colloidal solution and in the cells before experiments in animals.…”
Section: Cik Cells Labeled With Pegylated Aunprs For Photothermal Thementioning
confidence: 99%
“…Although CIK cells have the ability to kill cancer cells, the curative effect is not obvious in a short time. Current reports show that CIK cells own the ability to target in vivo tumor cells [15,16], homing to the tumor site through vascular perfusion. And the targeting characteristic of CIK cells has an extensive adaptability feature, which can be applied to clinical therapies of many kinds of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The main ligands recognized by NKG2D are MHC class I-related molecules A and B (MIC A/B) and members of the unique long 16-binding proteins, stress-inducible proteins expressed by tumor cells of various origin (3,4,(14)(15)(16)(17)(18). Recent clinical trials support their initial activity and excellent safety profile in challenging settings such as lung, renal, liver, breast and gastrointestinal cancers (19).…”
mentioning
confidence: 99%